(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Thrombotic Thrombocytopenic Purpura (TTP) is a rare, life-threatening disorder caused by ADAMTS13 deficiency, leading to uncontrolled platelet aggregation and microvascular thrombosis. It results in thrombocytopenia, hemolytic anemia, and organ damage, particularly affecting the kidneys and CNS. This study examines the relationship between platelet indices and renal dysfunction to improve disease understanding and management. Objective: To explore the correlation between the platelet parameters (such as Mean Platelet Volume) and renal function markers. Methodology: This combination of retrospective data from medical records and prospective follow-ups was used, focusing on laboratory results of platelet indices and renal function. Data collected from Shaikh Zaid Hospital. Descriptive statistical analysis was performed to determine the mean, standard deviation, and range for each parameter. Additionally, histograms and bar charts were used to illustrate the distribution patterns of age, platelet indices and renal function markers. Results: The study shows that there are notable variations in hemoglobin levels, platelet indices, and kidney parameters between the normal and abnormal groups. Anemia, elevated platelet production, and compromised renal function were seen in abnormal individuals. Its crucial involvement in TTP pathogenesis was validated by lower ADAMTS13 enzyme levels in the aberrant group. Conclusion(s): This study highlights the association between platelet indices and renal dysfunction in TTP, emphasizing their role in disease severity. Low platelet counts, elevated MPV, and renal impairment indicate complications, while ADAMTS13 variability suggests distinct patient subgroups, influencing diagnosis and treatment.